Exploiting Pitch Accent Information in Compound Processing: A Comparison between Adults and 6- to 7-Year-Old Children. Issue 4 (2nd October 2017) - Hirose, Yuki; Mazuka, Reiko
ABSTRACT: A noun can be potentially ambiguous as to whether it is a head on its own, or is a modifier of a Noun + Noun compound waiting for its head. This study investigates whether young children can exploit the prosodic information on a modifier constituent preceding the head to facilitate resolution of such ambiguity in Japanese. Evidence from English suggests that young speakers are not sensitive to compound stress in distinguishing between compounds and syntactic phrases unless the compound is very familiar (Good, 2008; Vogel & Raimy, 2002). This study concerns whether children in general have such limited capability to use prosodic cues to promptly compute a compound representation without the lexical boost, or whether they might show greater sensitivity to more categorical compound prosody such as that associated with the Compound Accent Rule (CAR) in Japanese. A previous study (Hirose & Mazuka, 2015) demonstrated that adult Japanese speakers can predict the compound structure prior to the head if the prosodic information on the modifier unambiguously signals that the CAR is being applied. The present study conducted the same on-line experiment with children (6- to 7-year-olds) and compared the time course of the effects with that of adults using permutation-based analysis (Maris & Oosternveld, 2007). The results reveal that children are sensitive to pitch accent information that facilitates the quicker processing of the compound or the single head noun representation compared to when such prosodic signals are less apparent, depending on the type of the lexical accent of the noun in question.